PERAN LEMBAGA KEUANGAN MIKRO DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI - Indarti, Dwi; Maulidiya, Erlina; Simorangkir, Christien; Saraswati, Birgitta Dian (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2022)
Economic growth is a measure of the welfare of the Indonesian people. Over time, the factors that affect economic growth are growing. The emergence of Microfinance Institutions (MFIs) has its own impact on Indonesia's economic growth. This study aims to determine the effect of Microfinance Institutions on economic growth in Indonesia. By using the Random Effect Model (REM) panel data regression method covering 21 provinces in Indonesia in the 2019-2020 period, this study shows that, only the Labor variable is proven to have an effect on economic growth in Indonesia. While the variables for the number of MFIs and the amount of MSME loan funds have not been proven to have an effect on economic growth in Indonesia. This indicates that the human resource factor as a form of human capital is the main factor driving economic growth in Indonesia. So that the policy implication of this research is to encourage economic growth a policy to improve the quality of human resources is needed. Keywords: Economic Growth, Total Microfinance, Labor, REM